Assessment of Agreement Between Peak Systolic Velocity of Inferior Thyroid Artery And Thyroid Scan In Differentiating Diffuse Toxic Goiter And Subacute Thyroiditis. (Bangladesh Journal of Nuclear Medicine, 2019)
Objective:To analyze agreement between Peak Systolic Velocity (PSV) of inferior thyroid artery (ITA) and Tc99m Thyroid Scan for evaluation of thyrotoxicosis(diffuse toxic goiter and sub-acute thyroiditis) Patients and Methods: This prospective cross sectional study was conducted in National Institute of Nuclear medicine and Allied sciences (NINMAS)From July 2016 to June 2017.Total sixty four patients with thyrotoxicosis were included in the study. History, clinical examination and thyroid function tests were done for all patients. The thyroid glands of all patients wereevaluated by gray scale ultrasonography for size, shapeand echotexture. Color-flow Doppler ultrasonographyof the thyroid tissue was performed and spectral flowanalysis of both inferior thyroid arteries were assessed. Tc99m Thyroid scan was done for all patients. The patients were divided into two groups. Group A- Diffuse toxic goiter(DTG) and Group B- Subacute thyroiditis(SAT).The diagnosis of diffuse toxic goiter and subacute thyroiditis was supported by the clinical picture, RAIU uptake and Thyroid Scan.Results:All patients had suppressed thyrotropin.Thyroid blood flow, measured by PSV of ITA (CFDS) was highthan normal in DTG patients, while low PSV ofITA than normal was found in SAT.According to Thyroid Scan,Radiotracer concentration (RTC)was diffusely increased with low BKG (background) and almost absent RTC with high BKG was noted in DTG and SAT respectively.In our study Tc99m Thyroid Scan shows agreement with Peak Systolic Velocity of ITA.Here Kappa value was 0.818 and 0.871 in DTG and SAT respectively with P value